Independent Reading as Critical Practice: Bridging Autonomy with Literary Theory and Criticism: - - Baihaqi Baihaqi; Saiful Anwar Matondang; M Manugeren (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
This study aimed to implement independent reading as a form of critical practice through the lens of literary theory and criticism among 30 eleventh-grade students at SMA Negeri 1 Langsa. The research sought to introduce independent reading not merely as a leisure activity but as a reflective and critical engagement with texts. Employing a qualitative case study design grounded in reader-response theory, the study examined a group of students, a reading program, and a classroom context where independent reading was practiced as critical literacy. Data were collected through classroom observations, semi-structured interviews, and document analysis, including students’ reading responses and assessment results. The findings indicate a measurable improvement in students’ reading performance, with pretest scores ranging from 45–80 (M = 61) and posttest scores ranging from 50–85 (M = 69). More importantly, the integration of literary theory within independent reading encouraged students to engage with texts from multiple perspectives, consider cultural contexts, and develop empathetic and interpretive awareness. These outcomes suggest that independent reading, when supported by literary theory and guided reflection, can function as an effective pedagogical strategy for fostering critical literacy in EFL classrooms. The study contributes theoretically by positioning independent reading as a critical-literary practice and pedagogically by demonstrating its potential to enhance students’ interpretive competence and engagement with literary texts.